Earth observation brain (EOB): an intelligent earth observation system - Deren Li; Mi Wang; Zhipeng Dong; Xin Shen; Lite Shi (Geo-spatial Information Science, 2017)
Since the twenty-first century, with the rapid development of high-resolution earth observation satellites, the earth observation satellite system has developed from the initial single satellite observation model to the current satellite constellation formed by light and small satellites observation model. All-weather and all-directional fine earth observation can now be realized. In the future, the satellite constellation, communication satellites, navigation satellites, and aircrafts are linked through dynamic linking network to form an air-space information network to realize real-time services of intelligent air-space information. To further enhance the perception, cognition, and quick response ability of the network, we propose the concept and model of the Earth Observation Brain (EOB) − the intelligent earth system based on events perception in this paper. Then, some key technologies needed to be solved in the EOB are also described. An application example is illustrated to show the process of perception and cognition in the primary stage of the EOB. In the future, EOB can observe what change of what object, the when and where to push these right information to mobile terminal of right people at the right time and right place. Global users can obtain any data, information, and knowledge in real-time through the EOB.